A Contrastive Analysis of the Category of Number in English and Albanian Nominal System - Canta, Agnesa (European Scientific Journal, ESJ, 2016)
English and Albanian as members of the Indo-European trunk of languages undoubtedly share certain characteristics, common for all members of this family of languages, but as two structurally different languages, they also show significant differences. The main aim of this paper is to highlight not only some of the differences, but also similarities in regard to the grammatical category of number in English and Albanian nominal system. The paper is based on various English and Albanian grammar books, written by prominent authors, which provide an abundance of data examined through the contrastive method. The results indicate that nouns in these two languages show differences which concern several aspects of the grammatical category of number. Some of these differences concern the way these two languages treat nouns in the singular and plural number, the ways of forming the plural number, and their usage with articles and numerals. One essential difference, however, concerns the collective and compound nouns which show an almost complete discrepancy in these two languages due to the ways they write these nouns, and the ways these nouns function in these languages. Nevertheless, in spite of the differences, there are also some similarities that concern mainly the ways of forming the plural number, but also the group of nouns used only in the singular called â€œsingularia tantumâ€, and those used only in the plural â€œpluralia tantumâ€.